The Impact of SDG12 on the Productivity of Firms and Consumption of Households - Alleah Samporna; Julius Patrick I. Buenabajo; Ma. Ella R Perez; Marie Antoinette L. Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2022)
Responsible Production and Consumption have had considerable roles in sustainable development and how it affects economic growth for the countries. Moreover, inefficient consumption patterns of businesses lead to significantly large amounts of waste and excessive use of scarce natural resources. Meanwhile, irresponsible production may cause environmental degradation, resource shortages, and health risks. This article outlines the fundamental characteristics of sustainable consumption and production in achieving the Sustainable Development Agenda target of